If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7r + -15 = 3r + 21 Reorder the terms: -15 + 7r = 3r + 21 Reorder the terms: -15 + 7r = 21 + 3r Solving -15 + 7r = 21 + 3r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-3r' to each side of the equation. -15 + 7r + -3r = 21 + 3r + -3r Combine like terms: 7r + -3r = 4r -15 + 4r = 21 + 3r + -3r Combine like terms: 3r + -3r = 0 -15 + 4r = 21 + 0 -15 + 4r = 21 Add '15' to each side of the equation. -15 + 15 + 4r = 21 + 15 Combine like terms: -15 + 15 = 0 0 + 4r = 21 + 15 4r = 21 + 15 Combine like terms: 21 + 15 = 36 4r = 36 Divide each side by '4'. r = 9 Simplifying r = 9
| -6(8f+3)=26-7f | | m3-7=-10 | | 6-2(x-3)+4=4(2-3x) | | 12=-2-4 | | 7y+6x=6 | | -9a+45=-18 | | 3xsquared-24x+45=0 | | 16=-8c+9c | | (9x+2)(9x-1)=9x^2+3x-2 | | Y=0(-3)+-4 | | 5(5x-6)=67.5 | | 3x^2+15x+30= | | 8(n+1)-1=3(8+3n)-3 | | -x-13=-31 | | -6=3u4+12 | | y=4(-3)+3 | | 3x^2+15x+25= | | -6x^2-20x+16=0 | | (9x+2)(9x-1)=x | | 3x-17=x-1 | | 16x^4-64=0 | | 2x+11=43-3x | | 15-2(4)= | | 4n+12=4n+12 | | h+11.3=-11.3 | | 15-2(2)= | | 3x-5=72 | | a(n+1)= | | h=-8t^2+63 | | F(x)=62+35log(11-4) | | 12x+3=32 | | -6+2(10)= |